(untitled) - Nguyen, Thi Thuy (Uppsala, Sweden, 2010)
This book evaluates preservation methods of catfish by-products (CBP), and the effects of replacing marine fish meal (FM) with these processing by products on diet digestibility, performance, feed efficiency and carcass quality in growing-finishing pigs
Keywords: Swine,Seafood industry,Heo,Ngành thủy sản; Feeding and feeds,By-products,Chăn nuôi và thức ăn,Phụ phẩm